2008
DOI: 10.21608/eajbsa.2008.15767
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the chitin synthesis inhibitor lufenuron (cga-184699) on growth, development and morphogenesis of Schistocerca gregaria (orthoptera: acrididae).

Abstract: Efficiency of the chitin synthesis inhibitor lufenuron (cga-184699) on growth, development and morphogenesis of Schistocerca gregaria (orthoptera: acrididae).ABSTRACT This paper deals with the objective of investigating the effects of Lufenuron (CGA-184699) on the growth, development and morphogenesis of the desert locust Schistocerca gregaria. Five concentration levels (1000, 500, 250, 125 and 62.5 ppm) were given through the fresh plant food to the newly moulted (4 th or 5 th ) instar or late-aged 5 th insta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
(31 reference statements)
1
8
1
Order By: Relevance
“…On the other hand, the present results of shortened larval duration and enhanced developmental rate of P. unionalis larvae were in agreement with the reported results of shortened larval duration of P. gossypiella after treatment of newly hatched larvae with Methoxyfenozide [99] and other insects, such as Rhynchophorus ferrugineus by Lufenuron and Diofenolan [121], A. ipsilon by Flufenoxuron [122] and Schistocerca gregaria by Lufenuron [123]. On the contrary, the present results disagreed with the reported results of prolonged larval duration of S. littoralis larvae after treatment of penultimate or last instar larvae with by Novaluron [55] and Cyromazine [78]; prolonged larval duration after treatment of 5 th instar larvae of Spodoptera frugiperda with LC 10 and LC 25 of Methoxyfenozide [124] and prolonged larval duration in P. gossypiella after treatment of the first instar larvae with Pyriproxyfen [99].…”
Section: Disturbance Of Growth and Development Of P Unionalis By Novsupporting
confidence: 93%
“…On the other hand, the present results of shortened larval duration and enhanced developmental rate of P. unionalis larvae were in agreement with the reported results of shortened larval duration of P. gossypiella after treatment of newly hatched larvae with Methoxyfenozide [99] and other insects, such as Rhynchophorus ferrugineus by Lufenuron and Diofenolan [121], A. ipsilon by Flufenoxuron [122] and Schistocerca gregaria by Lufenuron [123]. On the contrary, the present results disagreed with the reported results of prolonged larval duration of S. littoralis larvae after treatment of penultimate or last instar larvae with by Novaluron [55] and Cyromazine [78]; prolonged larval duration after treatment of 5 th instar larvae of Spodoptera frugiperda with LC 10 and LC 25 of Methoxyfenozide [124] and prolonged larval duration in P. gossypiella after treatment of the first instar larvae with Pyriproxyfen [99].…”
Section: Disturbance Of Growth and Development Of P Unionalis By Novsupporting
confidence: 93%
“…In addition, the present results of prolonged larval duration and regressed developmental rate of P. unionalis, after treatment of newly moulted last instar larvae with methoxyfenozide corroborated with the reported results of prolonged larval duration in some insect species by various IGRs, such as S. littoralis larvae after treatment of penultimate or last instar larvae with by novaluron (Ghoneim et al, 2015) and cyromazine (Tanani et al, 2015); Spodoptera frugiperda by Methoxyfenozide (Zarate et al, 2011) and P. gossypiella by pyriproxyfen (Sabry and Abdou, 2016) or noviflumuron and novaluron (Hamadah and Ghoneim, 2017). On the contrary, the present results disagreed with the reported results of shortened larval duration of some insects after treatment with different IGRs, such as Rhynchophorus ferrugineus by lufenuron and diofenolan (Tanani, 2001), A. ipsilon by flufenoxuron (El-Sheikh, 2002), Schistocerca gregaria by lufenuron (Bakr et al, 2008), P. gossypiella by methoxyfenozide (Sabry and Abdou, 2016) and P. unionalis by novaluron (Ghoneim et al, 2017b) As reported in the available literature, many IGRs exhibited some inhibitory Diflubenzuron (Aref et al, 2010), lufenuron (Gaaboub et al, 2012), novaluron (Ghoneim et al, 2015) and Cyromazine (Tanani et al, 2015); C. pipiens by kinoprene (Hamaidia and Soltani, 2014); A. ipsilon by methoprene and flufenoxuron (Khatter, 2014); P. gossypiella by buprofezin (Al-Kazafy, 2013); teflubenzuron (El-Khayat et al, 2015) and chromafenozide (Salem, 2015). Recently, the developmental duration was prolonged indicating a retarded development in some other insects by various IGRs, such as G. pyloalis by lufenuron (Aliabadi et al, 2016); C. pipiens by methoxyfenozide (Hamaidia and Soltani, 2016); C. cephalonica by fenoxycarb (Begum and Qamar, 2016); P. gossypiella by lufenuron and Pyriproxyfen (Sabry and Abdou, 2016), noviflumuron and novaluron (Hamadah and and Novaluron (Ghoneim et al, 2017a); and P. unionalis by novaluron (Ghoneim et al, 2017b); etc.…”
Section: Inhibited Growth and Retarded Development Of P Unionalis Bycontrasting
confidence: 99%
“…Higher mortality was recorded within 4-9 days in the treated 4 th nymphal instar of oriental migratory locust Locusta migratoria manilensis with Flufenoxuron and chlorbenzuron (Zhongren et al, 2002). Mortal activity of the chitin synthesis inhibitors (CSIs): Flufenoxuron (CAS-101463) and Lufenuron (CGA184699) on the penultimate instar nymphs of the desert locust Schistocerca gregaria increased proportionally to the concentration level of tested compounds (Bakr et al, 2008).…”
Section: Biological Studiesmentioning
confidence: 99%
“…Chitin synthesis inhibitors (CSIs) are usually classified in IGRs interfering with chitin biosynthesis in insects and thus prevent moulting, or produce an imperfect cuticle. These compounds have a good lethal effect on the desert locust (Azam and Seegh, 1993;Coppen and Jepson, 1996a;Bakr et al, 2008).…”
Section: Introductionmentioning
confidence: 99%